Strategi promosi pariwisata dalam perspektif ekonomi islam - Habiburahman, Habiburahman (Jurnal Ekonomi, 2017)
Tourist areas that have enough objects and attractions will have the potential to be developed. With the exploitation of tourism potential and opportunities into an industry, is expected to increase the income of the community and the region. The research sample this analysis is coast at Kalianda of South Lampung. The problems studied in this paper is how the implementation of promotional strategies that need to be done in improving tourism management. This study aims to determine the implementation ofÂ  tourism promotion strategies and supporting factors. Research with (field research) is qualitative, data collection using observation methods, interviews, and documentation. While the analysis using qualitative analysis (non statistics) which is descriptive qualitative, by using inductive thinking. Based on the results of research in coast at Kalianda of South Lampung, accordance with tourism promotion strategy in the perspective of Islamic economics that is honesty, sincerity and trust, and seen from the ethics of promotion in Islam also not sell out oath, not to promise, honest, Avoid fraud, and be willing to profit a little but a blessing.